160k views
5 votes
Helppppppppppppppppppppppppp

Helppppppppppppppppppppppppp-example-1
User Rehab
by
5.2k points

2 Answers

2 votes

Answer:

phonomath. it saves lives in math

User AdrianCooney
by
5.1k points
4 votes

Answer:

with the process for the first one you could do the others.


x=5 and
y=2

Explanation:

We have two linear equations


4x+3y=26 and
(y)/(3)=(x)/(3)-1

From the second equation we can find y then


y=3((x)/(3)-1)


y=3(x)/(3)-3


y=x-3

Now we use this expression of y in the first equation


4x+3y=26


4x+3(x-3)=26


4x+3x-9=26


7x=26+9


x=(35)/(7)


x=5

Now que can find the value of y


y=x-3


y=5-3


y=2

User Yam Marcovic
by
6.0k points